Energy optimization in process systems and fuel cells - Sieniutycz, Stanislaw; Jezowski, Jacek (Elsevier, 2018)
Energy Optimization in Process Systems and Fuel Cells, Third Edition covers the optimization and integration of energy systems, with a particular focus on fuel cell technology. With rising energy prices, imminent energy shortages, and the increasing environmental impacts of energy production, energy optimization and systems integration is critically important. The book applies thermodynamics, kinetics and economics to study the effect of equipment size, environmental parameters, and economic factors on optimal power production and heat integration. Author Stanislaw Sieniutycz, highly recognized for his expertise and teaching, shows how costs can be substantially reduced, particularly in utilities common in the chemical industry. This third edition contains substantial revisions and modifications, with new material on catalytic reactors, sorption systems, sorbent or catalyst regenerators, dryers, and more. Presents a unified approach to the optimization and integration of energy systemsIncludes a large number of examples treating dynamical systemsProvides exposition showing the power of thermodynamicsContains a large number of maximum power analyses and their extensions.